2020
DOI: 10.3389/fpubh.2020.590275
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Solutions Are Climate Solutions: Lessons From Reusable Gowns

Abstract: The COVID-19 pandemic has laid bare the inadequacy of the U.S. healthcare system to deliver timely and resilient care. According to the American Hospital Association, the pandemic has created a $202 billion loss across the healthcare industry, forcing health care systems to lay off workers and making hospitals scramble to minimize supply chain costs. However, as the demand for personal protective equipment (PPE) grows, hospitals have sacrificed sustainable solutions for disposable options that, although conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 18 publications
0
33
0
2
Order By: Relevance
“…Centralized drug purchase is the key link to reduce drug prices, rectify drug circulation orders, and standardize drug use. The American Medical Supply Chain Association reported that centralized procurement can save 10–35% of procurement expenditure for medical institutions every year ( 1 ). Unlike the centralized drug procurement in the United States, which is completely configured by the market, centralized drug procurement of China is a supporting policy in the national medical system reform.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Centralized drug purchase is the key link to reduce drug prices, rectify drug circulation orders, and standardize drug use. The American Medical Supply Chain Association reported that centralized procurement can save 10–35% of procurement expenditure for medical institutions every year ( 1 ). Unlike the centralized drug procurement in the United States, which is completely configured by the market, centralized drug procurement of China is a supporting policy in the national medical system reform.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The sudden increase in demand for isolation gowns at the onset of the COVID-19 pandemic was accompanied by a spike in the price of disposable gowns from $0.25 to $5 per gown, a prohibitive 2000% increase. 58 This expense was compounded by the estimated $202 billion loss across the health care industry as a result of the COVID-19 pandemic. 58 Given the continuous need for PPE when caring for COVID-positive patients, as well as the environmental benefits of reusable gowns compared to disposable gowns, the value proposition of reusable gowns has become more compelling than ever before.…”
Section: Or Wastementioning
confidence: 99%
“…58 This expense was compounded by the estimated $202 billion loss across the health care industry as a result of the COVID-19 pandemic. 58 Given the continuous need for PPE when caring for COVID-positive patients, as well as the environmental benefits of reusable gowns compared to disposable gowns, the value proposition of reusable gowns has become more compelling than ever before. 58 Carilion Clinic reported that reusable gowns cost only $0.39 per use (compared to $0.79 per use for disposable gowns), a cost savings of nearly 50%.…”
Section: Or Wastementioning
confidence: 99%
See 2 more Smart Citations